The Atlas of chick development - Bellairs, Ruth; Osmond, Mark (Elsevier/Academic Press, 2014)
The Atlas of Chick Development, Third Edition, a classic work covering all major event of chick development, is extensively updated with new and more detailed photographs, enlargements showing regions of special-interest and complexity, and new illustrations. The revised text and expanded illustrative material describe the intricate changes that take place during development, together with accounts of recent experimental and molecular research that has transformed our understanding of morphogenesis. These wide-ranging updates make this book an essential resource for development.